CHARACTERISTICS OF DIELECTRIC BARRIER DISCHARGE (DBD) AS AN OZONE GENERATOR REACTOR - Jaya, Gede Wiratma; Nur, Muhammad; Anggara, Andhika Dwi; Metungku, Nofrita Angelina; Kinandana, Andi Wibowo; Zahar, Intan; Zain, Alfatihatuz Zulfah (PPI Dunia, 2018)
Ozone is a gas formed from three oxygen atoms that are highly reactive and unstable compared to oxygen. Ozone can be generated by using a dielectric barrier discharge (DBD) generator. To know the ability of DBD reactor in producing ozone performed a characterization. Characterization is done by measuring the electrical current, electrical voltage, observing the plasma discharge, charge mobility, and ozone concentration. In this research using DBD reactor derived from the development of research Teaching Industry of  Diponegoro University. DBD reactor containof pyrex glass material as a dielectric barrier and parabolic wire made of aluminum as inner and outside electrodes in the dielectric barrier. DBD reactor was generated using high AC voltage of 2, 4, 6, 8, 10 and 12 kV and air flow rate is 10 L/min. The characterization results show that the higher the voltage can results increases of electrical current, for a discharge plasma produces a purplish color as a result of ionization process on the electrode. The calculation of charge mobility is  and the lowest and highest ozone concentration is 80 ppm and 280 ppm, respectively. In the future, application of DBD reactor has been characterized can be usedfor ozone gas production as food preservatives, improvement of the environmental quality of aquaculture and as an industrial and medical waste treatment system.